Sexual-risk behaviours and HIV and syphilis prevalence among in- and out-of-school adolescent girls and young women in Uganda: A cross-sectional study - Matovu, Joseph K. B.; Bukenya, Justine N.; Kasozi, Dickson; Kisaka, Stephens; Kisa, Rose; Nyabigambo, Agnes; Tugume, Abdulaziz; Bwanika, John B.; Mugenyi, Levicatus; Murungi, Irene; Serwadda, David; Wanyenze, Rhoda K. (PLoS ONE, 2021)
Adolescent girls and young women (AGYW) are at increased risk of sexually transmitted infections (STIs). We assessed sexual-risk behaviours and HIV and syphilis prevalence among AGYW in Uganda to inform the design of target-specific risk-reduction interventions. Methods This analysis utilizes data from 8,236 AGYW aged 10–24 years, collected in 20 districts, between July and August 2018. AGYW engaged in sexual-risk behaviour if they: a) reported a history of STIs; or b) had their sexual debut before age 15; or c) engaged in sex with 2+ partners in the past 12 months; or c) did not use or used condoms inconsistently with their most recent partners. We diagnosed HIV using DetermineTM HIV-1/2, Stat-PakTM HIV-1/2 and SD Bioline. We used SD Bioline Syphilis test kits to diagnose syphilis and Treponema Pallidum Hemagglutination Assay for confirmatory syphilis testing. Comparison of proportions was done using Chi-square (χ2) tests. Data were analysed using STATA (version 14.1). Results Of 4,488 AGYW (54.5%) that had ever had sex, 12.9% (n = 581) had their sexual debut before age 15; 19.1% (n = 858) reported a history of STIs. Of those that had ever had sex, 79.6% (n = 3,573) had sex in the 12 months preceding the survey; 75.6% (n = 2,707) with one (1) and 24.2% (n = 866) with 2+ partners. Condom use with the most recent sexual partner was low, with only 20.4% (n = 728) reporting consistent condom use while 79.6% (n = 2,842) reported inconsistent or no condom use. In-school AGYW were significantly less likely to have ever had sex (35.6% vs. 73.6%, P<0.001), to have had sexual debut before age 15 (7.7% vs. 15.5%, P<0.001) or to engage in sex with 2+ partners (5.3% vs. 15.8%,
Keywords: Sexual-risk behaviours; HIV and syphilis prevalence among AGYW in Uganda